Sustainable Water Infrastructure for Urbanizing Regions: Design and Validation of Aba North’s Multi-Component Supply System - Uchenna Ukpai; Isaac Enuma; Daniel Ulokaji; Aisosa Edokpayi; Idonije Edward (International Journal of Scientific Research in Civil Engineering, 2025)
Access to clean and safe drinking water is essential for public health and sustainable urban development. This study focuses on the design of components of a surface water-based municipal water supply scheme for Aba North LGA in Abia State, using Aba River as the raw water source. The objective was to develop an efficient and sustainable water supply system comprising an intake structure, water treatment plant, pumping station, storage facility, and distribution network to meet the daily water demand of the community. The methodology involved the design of a river intake structure to withdraw raw water efficiently. A water treatment plant was designed, incorporating screening, pre-sedimentation, coagulation, flocculation, sedimentation, and disinfection to ensure water quality. A pumping station was developed, considering static head, friction losses, velocity head, and total head, with an appropriate pump capacity to ensure adequate water conveyance. The storage system included an elevated tank to regulate water supply, and the distribution network was designed using EPANET to ensure efficient water delivery across the study area. Simulation results showed that the designed system effectively met the required hydraulic performance criteria. The pressure values ranged from 13.94 m to 22.88 m, while velocity values ranged from 0.19 m/s to 1.09 m/s, ensuring adequate water flow across the network. The total pipe length covered 35,110 m, demonstrating the system’s ability to deliver water efficiently. The study concludes that the proposed design is capable of meeting the water demand of Aba North LGA, providing a reliable and sustainable water supply system for the community.